Hollow Cathode Deposition of Thin Films - Gustavsson, Lars-Erik (Uppsala universitet, Fasta tillståndets elektronik, 2006)
Thin films of metals and compounds have a very wide range of applications today. Many of the deposition methods used for the production of such films utilize plasma to support the growth the film, e.g. by the supply of energy and the enhancement of reactivity. This thesis focuses on the physical vapor deposition (PVD) of thin films by high density plasma sources based on hollow cathodes and aims to increase the understanding of the deposition process and its influence on the film properties. Titanium nitride films reactively deposited by the low-pressure hybrid plasma (HYP LP) source exhibited excellent properties and was deposited at considerable higher rates than films deposited by conventional methods. An original finding in this work is the influence of substrate material on the deposition process and consequently on the properties of the deposited film. In the deposition of TiN films by the HYP LP source it was found that the substrate temperature was higher for Si substrates than for steel substrates due to a more efficient absorption of microwave power in Si than in steel. Further, it was found that ferromagnetic substrates influence the film growth in magnetized plasma systems. An effect of the ferromagnetic substrates is the enhancement of ion bombardment that increases the growth temperature and affects the texture and morphology of the growing films. It was also found that a DC bias can change the TiN film properties considerably and compensate the effect of ferromagnetic substrates. High rate depositions of chromium and chromium nitride films by the RF hollow cathode plasma jet (RHCPJ) source were studied. The performance of the reactive diffuse arc process and the CrN film properties indicates that the process can be transferred from small cylindrical cathodes to linear magnetized hollow cathodes which allow deposition on considerable larger areas and this is important for industrial applications.